lim x tends to -p. (x4 - p4) ÷ (x3 + p3)
Answers
Answered by
3
since it is 0/0 form... hence applying L hop.method
![( {x}^{4} - {p}^{4} ) \div ( {x}^{3} - {p}^{ 3} ) \\ = (4 {x}^{3} \div 3x {}^{2} ) \\ = (4 \div 3)x \\ limx = p \\ = 4p \div 3 ( {x}^{4} - {p}^{4} ) \div ( {x}^{3} - {p}^{ 3} ) \\ = (4 {x}^{3} \div 3x {}^{2} ) \\ = (4 \div 3)x \\ limx = p \\ = 4p \div 3](https://tex.z-dn.net/?f=%28+%7Bx%7D%5E%7B4%7D++-++%7Bp%7D%5E%7B4%7D+%29+%5Cdiv+%28+%7Bx%7D%5E%7B3%7D++-++%7Bp%7D%5E%7B+3%7D+%29+%5C%5C++%3D+%284+%7Bx%7D%5E%7B3%7D++%5Cdiv+3x+%7B%7D%5E%7B2%7D+%29+%5C%5C++%3D+%284+%5Cdiv+3%29x+%5C%5C+limx+%3D+p+%5C%5C++%3D+4p+%5Cdiv+3)
here is your answer.... mark as brainliest if helped
here is your answer.... mark as brainliest if helped
ayush493:
i am a commerce student & there is nothing like l lop
Similar questions